2014
DOI: 10.1186/preaccept-1290570722137060
|View full text |Cite
|
Sign up to set email alerts
|

Application of qPCR in conjunctival swab samples for the evaluation of canine leishmaniasis in borderline cases or disease relapse and correlation with clinical parameters

Abstract: Background: In leishmaniasis caused by Leishmania infantum, the dog acts as the main reservoir for the disease. Non-invasive sampling for Leishmania detection is pivotal for rapid and affordable diagnosis. Recently, the use of conjunctival swab (CS) has been evaluated as a non-invasive sampling technique for quantitative real-time PCR (qPCR). However, few investigations have been made on the applicability of CS qPCR in particular cases such as dogs with borderline IFAT titres, suspected disease relapse with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Moreover, the diagnosis of L . infantum infection was confirmed by a real-time PCR assay from conjunctival swabs and lymph nodes [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the diagnosis of L . infantum infection was confirmed by a real-time PCR assay from conjunctival swabs and lymph nodes [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Recently, other body samples, such as conjunctival swabs, are being considered as a source for CL tests but will require further research [ 45 , 46 ].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…β-actin or beta-2-microglobulin), not only to monitor PCR inhibition (i.e. false-negative results), but also to normalize the parasite load to the amount of host cells [ 33 , 34 , 48 , 58 ]. Although some clinical samples may contain a small amount of parasite DNA, the use of high copy number sequence as targets (e.g.…”
Section: Clinical Samplesmentioning
confidence: 99%
“…We also tested the use of conjunctival swabs (CS) for the evaluation of CanL by qPCR targeting kDNA. Since we used raw CS lysates as source of Leishmania DNA, their potential inhibition in qPCR was tested: it was found that 1 μl raw lysate per 25 μl qPCR reaction mixture did not show any inhibitory effect on the assays, allowing accurate quantification [ 48 ].…”
Section: Qpcr Assays For Parasite Detection and Quantificationmentioning
confidence: 99%